Research on the Path of Effective Management under New Vision - Wang, Jinhui (Pacific International Journal, 2024)
In today’s rapidly evolving business landscape, traditional management approaches are facing new challenges and difficulties. Effective management has become a critical element for organizational success, yet achieving it within the new environment remains a complex issue. This paper explores the path to effective management under the emerging integrated perspective. Through a comprehensive literature review and empirical research, the study identifies several key strategies that can help organizations navigate the new realities, including building adaptive organizations, strengthening communication and collaboration, promoting innovation and change, developing leadership capabilities, and fostering learning-oriented cultures. Drawing on modern management theory, innovation management, organizational behavior, and leadership frameworks, the research constructs a holistic theoretical foundation. The analysis of case studies across diverse sectors, such as information technology, cross-cultural management, strategic management, and knowledge management, reveals both the advantages and limitations of these theories in practical application. The findings suggest that the path to effective management is multifaceted, requiring the strategic and integrated deployment of various management practices. By examining the management approaches of successful organizations, the study proposes actionable strategies to help enterprises enhance their performance and competitiveness in the new era. The insights from this research are expected to provide valuable reference and practical guidance for organization leaders, supporting their efforts to achieve greater development and progress in the face of emerging challenges.